Stage direction as a component of the world of modern Ukrainian drama (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article analyzes stage direction as a means of actualization of charactersʼ conversational turns, as a component of authorʼs linguistic expression; it provides the main types of stage directions in modern Ukrainian dramatic discourse; it also detects fictionalized stage directions as a means of reinforcing the authorʼs position; it determines the ways a classical stage direction turns into a fictionalized one.
Keywords: stage direction; fictionalized stage direction; dramatic text; author; linguistic expression